2019
DOI: 10.3892/ol.2019.10953
|View full text |Cite
|
Sign up to set email alerts
|

A subset of patients with MSS/MSI‑low‑colorectal cancer showed increased CD8(+) TILs together with up‑regulated IFN‑γ

Abstract: A small subset of patients with proficient mismatch repair (pMMR)/microsatellite stable (MSS)-colorectal cancer (CRC) benefit from immunotherapy with anti-programmed cell death 1 (PD-1)/programmed death ligand 1 (PD-L1) blockade. Therefore, the aim of the current study was to evaluate the immune status of patients with pMMR/microsatellite instability-low (MSI-L)/MSS-CRC and deficient MMR (dMMR)/MSI-high (MSI-H)-CRC in order to identify responders to anti-PD-1/PD-L1 inhibitors. The current study used a dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 55 publications
(68 reference statements)
6
27
0
Order By: Relevance
“…Consistent to our results, previous studies showed that the CD8 T effector gene signature was significantly upregulated in MSI-H tumors compared with MSI-L/MSS tumors [ 28 ]. Moreover, a report demonstrated that CD8(+) cytotoxic T lymphocytes may lead to increased platelet destruction in immune thrombocytopenia [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent to our results, previous studies showed that the CD8 T effector gene signature was significantly upregulated in MSI-H tumors compared with MSI-L/MSS tumors [ 28 ]. Moreover, a report demonstrated that CD8(+) cytotoxic T lymphocytes may lead to increased platelet destruction in immune thrombocytopenia [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite advances in understanding of MSI at the genomic level, the process and mechanisms at the transcriptomic level remain relatively understudied. Researches on the anti-tumor effects of MSI have suggested an increased activation and infiltration of immune cells, together with an enhanced cytolytic activity as well as an up-regulation of CD8 + T-effector genes 29 , 43 . Remarkably, by analyzing the WGCNA-identified modules, the pathological signatures were demonstrated with high relevance to the expression level of IFN-γ-JAK-STAT1 signaling pathway, whose pivotal role in immune activation and response to immunotherapy has been supported by extensive evidence 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of CRC cases, MSS or pMMR CRC, are naturally resistant to immunotherapy; at least in part due to the low antigenicity (TMB) of the malignancy. However, based on TCGA dataset analysis, a small subset of patients among MSI-Low/MSS-CRC cases exhibiting a high CD8 + T cell infiltrate and an upregulation of IFN-γ could benefit from immunotherapies ( 98 ).…”
Section: The Paradox Of Colon Cancermentioning
confidence: 99%